Atopic Dermatitis in Latin America: A Roadmap to Address Data Collection, Knowledge Gaps, and Challenges. (3rd November 2022) - Borzutzky, Arturo; Larco, Jose Ignacio; Luna, Paula C.; McElwee, Elizabeth; Pires, Mario Cezar; Rico Restrepo, Mariana; Saez-de-Ocariz, Marimar; Sanchez, Jorge
Abstract : Background: Atopic dermatitis (AD) is a systemic, multifactorial disease that causes significant morbidity and health care burden in Latin America (LA). Data on AD are scarce in LA. Lack of disease registries and non-standardized study methodologies, coupled with region-specific genetic, immunological, and environmental factors, hamper data collection. A panel of LA experts in AD was given a series of relevant questions to address before a conference. Each narrative was discussed and edited through numerous rounds of deliberation until achieving consensus. Identified knowledge gaps in AD research were updated prevalence, adult-disease epidemiology, local phenotypes and endotypes, severe-disease prevalence, specialist distribution, and AD public health policy. Underlying reasons for these gaps include limited funding for AD research, from epidemiology and public policy to clinical and translational studies. Regional heterogeneity requires that complex interactions between race, ethnicity, and environmental factors be further studied. Informed awareness, education, and decision making should be encouraged.